Can informal redistribution withstand formal safety nets? Insights from urban-rural transfers in Burkina Faso - Michael Grimm; Renate Hartwig; Ann-Kristin Reitmann; Fadima Yaya Bocoum (Universität Passau, Wirtschaftswissenschaftliche Fakultät, 2020)
Households in rural areas still depend on informal transfers to meet subsistence needs and cope with shocks. Yet, to provide additional monetary support, formal safety nets are increasingly introduced in developing countries. However, it remains unclear whether such social protection policies will have the desired welfare effects. This article addresses this question by analyzing the private transfer response to changes in the income of rural recipients using novel data from Burkina Faso. We assume that the transfer-income relationship is a non-linear one where transfer motives, and therefore also transfer responses, vary with the recipient's position in the income distribution. Our findings support this view. We find a pronounced, negative private transfer response among the poorest of the poor. This observation has important policy implications, because those households that depend most on private transfers, would be most affected by crowding-out effects. In terms of transfer motives, the negative relationship for the lowest income class is consistent with transfers being altruistically motivated. With increasing income levels, transfers cease being altruistic at the margin and switch toward exchange motives. However, the observed transfer pattern is also indicative of an (informal) insurance role of private transfers. Rural households receive higher private transfers in response to negative shocks. These results can serve as a basis for the design of formal social protection mechanisms in a context where informal redistribution still plays an important role.
Keywords: D64; H31; I30; O12; 330; private transfers; crowding-out; sharing norms; informal insurance; Burkina Faso